Redirecting adenoviruses to tumour cells using therapeutic antibodies: Generation of a versatile human bispecific adaptor. Issue 2 (December 2015) - Vasiljevic, Snezana; Beale, Emma V.; Bonomelli, Camille; Easthope, Iona S.; Pritchard, Laura K.; Seabright, Gemma E.; Caputo, Alessandro T.; Scanlan, Christopher N.; Dalziel, Martin; Crispin, Max
Highlights: The therapeutic targeting of viruses to cancer cells is challenging. Virus are shown to be targeted using unmodified clinical antibodies and a humanized adaptor. Serum IgG can also be modulated to further enhance targeting. Adaptors suggest a general route to novel combination therapies against cancer. Abstract: Effective use of adenovirus-5 (Ad5) in cancer therapy is heavily dependent on the degree to which the virus's natural tropism can be subverted to one that favours tumour cells. This is normally achieved through either engineering of the viral fiber knob or the use of bispecific adaptors that display both adenovirus and tumour antigen receptors. One of the main limitations of these strategies is the need to tailor each engineering event to any given tumour antigen. Here, we explore bispecific adaptors that can utilise established anti-cancer therapeutic antibodies. Conjugates containing bacterially derived antibody binding motifs are efficient at retargeting virus to antibody targets. Here, we develop a humanized strategy whereby we synthesise a re-targeting adaptor based on a chimeric Ad5 ligand/antibody receptor construct. This adaptor acts as a molecular bridge analogous to therapeutic antibody mediated cross-linking of cytotoxic effector and tumour cells during immunotherapy. As a proof or principle, we demonstrate how this adaptor allows efficient viral recognition and entry into carcinoma cells through the therapeutic monoclonal antibodies Herceptin/trastuzumab and bavituximab. We show that targeting can be augmented by use of contemporary antibody enhancement strategies such as the selective elimination of competing serum IgG using "receptor refocusing" enzymes and we envisage that further improvements are achievable by enhancing the affinities between the adaptor and its ligands. Humanized bispecific adaptors offer the promise of a versatile retargeting technology that can exploit both clinically approved adenovirus and therapeutic antibodies.